Effect of water pollution by zinc on common carp (Cyprinus carpio) biochemical parameters and glutathione peroxidase and metallothionein gene expression - AL-Zamili, Hussein Ali Awadh; Hameed, Sadik (Brawijaya University, 2025)
Zinc is considered an essential mineral, in addition to being a toxic metal that causes serious diseases in humans and animals. Fingerlings of Cyprinus carpio were acquired from a nearby fish hatchery. The experimental fish's morphometric features were noted. All fish were stocked, regardless of gender. The fish were exposed to different concentrations (75, 100, 125, 150, and 175 mg/L) of Zn to obtain the LC50 for 96 hr. The median lethal concentration of Zn was 150 mg/L through 96 hours. As recorded, the fish were exposed to three safe concentrations, 10 mg/L, 30 mg/L and 50 mg/L. The results after 3 and 6 weeks were as follows: When compared to the control groups, all treated groups had significantly higher levels of ALT, AST, and MDA. While catalase was lower than control in some treated groups, GPX results were substantially higher in all treatment groups compared to control groups, and the concentration of MT increased in the treated groups. Glutathione peroxidase (GPX) and metallothionein (MT) gene expression in the blood are markers for metal pollution and abiotic stressors. These changes are trustworthy indications of the cellular and humoral immune responses in Cyprinus carpio. Blood levels of glutathione peroxidase (GPX) and metallothionein (MT) signal exposure to metals and other environmental stresses. These alterations in Cyprinus carpio are reliable markers of the humoral and cellular immune responses.